Nicholas Nickleby, Adaptation, Rehearsal and Catharsis - Luc Bouvard (Cahiers Victoriens et Edouardiens)
Nicholas Nickleby might very well be Dickens’s most theatrical novel, from a formal as well as thematic point of view. Each one of the various film adaptations of the novel this paper addresses focuses on a specific aspect. The 1947 Cavalcanti version uses the film to clearly state its adaptation process and flaunt its formal independence from the initial literary text while the Jim Goddard shooting of the David Edgar-Trevor Nunn-John Caird’s 9-hour long adaptation stands as a Marxist manifesto. The recent B.B.C. version directed by Stephen Whittaker dwells on the Nicholas-Smike didactic relationship and Douglas McGrath seems to continue along that line while stressing the pseudo-psychoanalytical relationship between the two characters. Each seems to have revisited the novel, not so much in terms of cardinal functions as in terms of catalysers and integrational functions, changing not the plot but the psychological and social emphases.